Surface integrity of milling in-situ TiB2 particle reinforced Al matrix composites. (January 2016) - Xiong, Yifeng; Wang, Wenhu; Jiang, Ruisong; Lin, Kunyang; Song, Guodong
Abstract: The preparation process and material properties of in-situ TiB2 particle reinforced Al matrix composites are quite different from conventional ex-situ Al matrix composites (SiCp /Al composites). Most researches have been carried out mainly focus on the machinability of SiCp /Al composites, but few studies about the machinability of in-situ TiB2 particle reinforced Al matrix composites have been published. To address this issue, experimental researches were conducted to investigate the surface integrity (surface roughness, residual stress, microhardness, surface topography, defects) of milling in-situ TiB2 particle reinforced Al matrix composites in this paper. By examining the machined surface with SEM and EDS for different machining parameters, the influences of cutting speed, feed rate, cutting depth and width on surface integrity were investigated. The results show that feed rate has the dominant influence on surface roughness. As the feed rate increases, the surface roughness increases accordingly. Residual stress decreases and transfers from compressive stress to tensile stress as milling speed gets larger and feed rate decreases. Microhardness variation is not evident below the machined surface. Besides, unlike ex-situ Al matrix composites, pull-out or fractured particles were rarely found on the machined surface of in-situ TiB2 /Al composites. Highlights: Investigations are carried out on In-situ TiB2 /Al composites whose cutting performance hasn't been studied widely yet. Unlike conventional ex-situ SiCp /Al composites, there is no sign of pull-out or fractured particles on the machined surface. There are compressive and tensile stress in the machined surface which is also different from that of SiCp /Al composites. No obvious softening and hardening is found below the machined surface.